'The little that I have done is already gone and forgotten':Farinelli and Burney Write Music History. (12th November 2015) - Desler, Anne
Abstract: Eighteenth-century narratives of Carlo Broschi Farinelli's inimitability and superiority did not arise fortuitously but resulted to a large extent from artistic, professional and personal choices made by the singer in order to create a unique artistic profile and influence public perception of him. Similarly, Charles Burney created his historical writings with the aim of establishing himself as a man of letters in order to rise in social status and leave a lasting legacy. Analysis of Farinelli's careful manipulation of his reputation in his encounters with Burney and the latter's calculated representation of Farinelli in The Present State of Music in France and Italy and A General History of Music sheds light not only on both men's self-promotion strategies, but also on the high degree of mediation of historical fact in writings that have long served as supposedly reliable 'primary' sources on eighteenth-century music.